The plantain proteome, a focus on Allele specific proteins obtained from plantain fruits - Campos, N.A.; Swennen, Rony L.; Carpentier, Sebastien C. (Wiley, 2018)
Proteomics has been applied with great potential to elucidate molecular mechanisms in plants. This is especially valid in the case of non-model crops of which their genome has not been sequenced yet, or is not well annotated. Plantains are a kind of cooking bananas that are economically very important in Africa, India, and Latin America. The aim of this work was to characterize the fruit proteome of common dessert bananas and plantains and to identify proteins that are only encoded by the plantain genome. We present the first plantain fruit proteome. All data are available via ProteomeXchange with identifier PXD005589. Using our in-house workflow, we found 37 alleles to be unique for plantain covered by 59 peptides. Although we do not have access (yet) to whole-genome sequencing data from triploid banana cultivars, we show that proteomics is an easily accessible complementary alternative to detect different allele specific SNPs/SAAPs. These unique alleles might contribute toward the differences in the metabolism between dessert bananas and plantains. This dataset will stimulate further analysis by the scientific community, boost plantain research, and facilitate plantain breeding.